Campesino and indigenous women conserve floral species richness for pollinators for esthetic reasons - Kolze, Anna Lena; Philpott, Stacy M.; Rivera-Pedroza, Leonardo F.; Armbrecht, Inge (Frontiers in Sustainable Food Systems, 2023)
Homegardens in agricultural areas are important refuges for pollinators and other valuable species due to the extensive plant diversity therein. Yet, plant diversity may strongly depend on the identity of the gardeners and their knowledge of plant identification and plant uses. In this study, we used botanical surveys and homegardener interviews to explore plant diversity in homegardens in coffee-producing regions of Colombia, and to examine how homegardener identity influences their knowledge of plants, plant uses, and motivations for maintaining a homegarden. We collected information in three villages in Cauca, Colombia and interviewed campesino (n = 30) and indigenous (n = 30) homegardeners. Half of the respondents from each social group were women and half were men. Of the 566 plant species that we detected in botanical surveys, the most recognized spontaneous herbs among homegardeners were “papunga” (Bidens pilosa, n = 38), “lechuguilla" (Emilia sonchifolia, n = 32), and “escoba” (Sida acuta, n = 31). Homegardeners identified multiple uses of spontaneous herbs including for food, material, medicine, plants for bees, and other environmental, conservation, or social uses. In addition, three different groups of gardeners emerged from social groupings and interview responses: 1) indigenous men with little knowledge of the uses of spontaneous herbs; 2) indigenous and campesino women who considered it beneficial to have flowers and crops for pollinators; and 3) male farmers who described detailed mutualistic plant-pollinator interactions that benefit crops, and who use spontaneous herbs to maintain soil moisture. In conclusion, homegardeners kept very diverse gardens and identified spontaneous herbs and pollinator functions, but this strongly depended on age, knowledge, and social group. Thus, homegarden presence within agricultural landscapes is of great importance to sustain functional biodiversity and ecosystem services in Colombian agroecosystems.